Conformación de un centro de capacitación popular permanente en el Cantón Quito provincia de Pichincha - Armas Baños, Sandra Elizabeth (2014)
It is a project-school Compensatory Education for the implementation of specific programs in marginal urban and rural sectors, and help strengthen and comparison of studies in the field of compensatory education, with regular regime.